Pipe sharing: A capacity allocation method for incorporating economy and fairness in the multiproduct pipeline - Li, Zhengbing; Liao, Qi; Zhang, Hao; Zhang, Jicai; Tu, Renfu; Liang, Yongtu (Energy (Oxford), 2024)
To guarantee fair access to pipeline facilities, pipe companies around the world have promoted market-based reform measures that are subject to governmental regulation. The pipe company should allocate transport capacity to shippers based on their nominations and then make schedules that align with the operational process. The reasonable mechanism is crucial for allocation results, affecting the carrier's revenue and shippers' fairness. Aiming at this issue, this paper puts forward an allocation mechanism of combining priority rules with historical data based on summarizing existing mechanisms. A multi-objective optimization model for capacity allocation that simultaneously considers economic and fairness metrics is developed. Finally, the efficient frontiers describing the economy-fairness trade-off are generated through using ε-constraint method, which can be selected by the pipe company based on its preference. Using data from a real pipeline as a case study, the solutions under different mechanisms are quantitatively evaluated. The results show that different mechanisms are applicable differently. Compared with other existing mechanisms, the proposed mechanism brings the pipe company the maximum cost of 1665.98 × 104CNY. On the basis of realizing the fair allocation, the proposed method ensures the pipe company to obtain the maximum transport cost to a certain extent as well. •Propose a new allocation mechanism of combining priority rules with historical data.•Develop a capacity allocation method that simultaneously considers economy and fairness.•Compare the results under six allocation mechanisms for quantitative analysis.•Maximum increase of 93.7 % in optimal fairness on capacity allocation for shippers.